Q: 3N plus 2N plus 3

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3 + 3n = 9 + 2n + 4n n = -2

3n + 9 = 3(n + 3)

3n+3=n+7 3n+3-n=n+7-n (subtract n from both sides) 2n+3=7 2n+3-3=7-3 (subtract 3 from both sides ) 2n=4 2n/2=4/2 (divided by 2 on both the sides) n=2 Answer: n=2

5n + 1 = 10 + 2n5n - 2n + 1 - 1 = 10 - 1 + 2n - 2n3n = 93n/3 = 9/3n = 3

The question seems ambigous, but I will consider n 2n to be solving for n:2n - 3n = n/3 + 14-n = n/3 + 14-3n = n + 42-4n = 42Thus, the solution is n = -42/4 = -21/2 = -10.5.

Related questions

3 + 3n = 9 + 2n + 4n n = -2

3n + 9 = 3(n + 3)

3n - 2n = n 3n - 2n = (3 - 2)n = 1n = n

3n+3=n+7 3n+3-n=n+7-n (subtract n from both sides) 2n+3=7 2n+3-3=7-3 (subtract 3 from both sides ) 2n=4 2n/2=4/2 (divided by 2 on both the sides) n=2 Answer: n=2

If you mean: (2n-14)(3n+9) = 0 then it is a quadratic equation whose solution is n = -3 or n = 7

5n + 1 = 10 + 2n5n - 2n + 1 - 1 = 10 - 1 + 2n - 2n3n = 93n/3 = 9/3n = 3

15/6n + 6/6n = 21/6n = 7/2n

The question seems ambigous, but I will consider n 2n to be solving for n:2n - 3n = n/3 + 14-n = n/3 + 14-3n = n + 42-4n = 42Thus, the solution is n = -42/4 = -21/2 = -10.5.

3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (3n + 3 - 3n + 1) = 3n + 2 + (4) = 3n + 6

41 - 2n = 2 + n Add 2n to each side: 41 = 2 + 3n Subtract 2 from each side: 39 = 3n Divide each side by 3: 13 = n

7-2n=n-147-2n+2n=n-14+2n7=3n-147+14=3n21=3n21/3=3n/37=n

9+2n=5n this is how you would set up the problem 9+2n-2n=5n-2n then you subtract the number with the variable on each side 9=3n this is what it leaves you with 9/3=3n/3 then you divide three by both sides to get the variable by itself 3=n then you have your answer Hope this helps you!!